P-106 Survival Analysis in Brazilian Cohort. Impact of Biological Therapy in Disease Duration Until Surgery. (February 2017) - Kotze, Paulo; Magro, Daniela; Kotze, Lorete; Saab, Mansur; Saab, Barbara; Olandoski, Marcia; Pinheiro, Lilian; Martinez, Carlos Augusto; Ayrizono, Maria de Lourdes; Coy, Claudio
Abstract : Background: The indications for biological agents in Crohn's Disease (CD) are mainly focused on the severe forms of the disease. Frequently, a patient needs some form of surgical treatment during the use of this class of medications. This study aimed to identify if preoperative biologics have an impact on disease duration until surgery, as well as to outline possible risk factors for intestinal resections in CD. Methods: This was an observational retrospective study with CD patients submitted to intestinal resections due to complications or failure to medical therapy in a period of 7 years. They were allocated in 2 groups according to previous exposure to anti-TNF agents in the preoperative period. Epidemiological aspects regarding age at diagnosis, malnutrition, use of azathioprine and perianal disease were considered. Kaplan-Meier survival analysis was used to outline possible differences between the groups regarding the disease duration and surgery. Results: A total of 123 patients were included (52 without and 71 with previous exposure to biologics). The groups were considered homogeneous, except for perianal CD, previous use of azathioprine, presence of intestinal stoma and age. Patients with previous biologics were younger (mean age 25 ± 1.47 × 30 ± 1.78) (Log-rank P = 0.046). Disease duration until surgery was 108 ± 6, 9 months, max 276 months. The survival estimation found no difference in the mean time to intestinal resection between the groups (100.5 ± 10.8 months in patients without and 114.0 ± 9.07 months in patients with previous biologics) ( P = 0.48). Malnutrition was identified in 34.6% and 25.3% of the patients without and with previous biologics, respectively ( P = 0.35). In patients with stomas, there was longer disease duration when biologics were used (101.4 ± 7.5 × 138.2 ± 16.1 months) (Log-rank P = 0.04). There was no difference in disease duration between the groups regarding perianal CD (101.6 ± 8.9 × 118.6 ± 10.6 months) ( P = 0.49) and use of azathioprine ( P = 0.35). Conclusions: Disease duration from diagnosis to surgery was not influenced by preoperative use of biological therapy in this cohort of patients. Patients in use of biological therapy have delayed the stoma construction.